Enhancing accuracy and efficiency in upper extremity disability assessments: development and testing of a desktop application - Emre Ozmen; Gamze Gül Güleç; Hazal İzol Özmen; Melih Civan; Esra Circi; Serdar Yuksel; Alican Baris (AVES YAYINCILIK A.Ş., 2025)
This study aimed to validate a software application (app) developed by the authors to streamline and enhance the accuracy of disability assessments, specifically for musculoskeletal system disabilities in the upper extremities. A software was developed under a TÜBİTAK-funded project to aid in the disability assessment process. This tool, designed for Windows operating systems and developed in Visual Basic (VB.NET), was tested using archive data from 50 patients, focusing on upper extremity physical evaluations. Statistical analysis, including the Shapiro-Wilk and Independent t-test/Mann-Whitney U-tests, was conducted using IBM SPSS Statistics to compare the app-assisted and manual assessment methods regarding time and rating'. Significant time-saving was observed with the app-assisted method, which was 328.3 seconds faster on average than the manual method. The average rating difference between the 2 methods was minor (0.40 points, 0.92% difference) and not statistically significant (P=.931). The app-assisted method showed efficiency in disability assessment with comparable accuracy to the manual methods. This application was developed for physicians who examine patients with musculoskeletal system disabilities in the upper extremities for the Health Board. Our results show that the application reduces the average evaluation time by 5 minutes while maintaining accuracy comparable to the manual method. It could be a helpful tool for physicians in a clinical setting. Level IV, Diagnostic Study.
Keywords: Orthopedic surgery; RD701-811; Research Article